Highly aligned 2D NV ensemble fabrication from nitrogen-terminated (111) surface. (15th August 2021) - Tatsuishi, Tetsuya; Kanehisa, Kyotaro; Kageura, Taisuke; Sonoda, Takahiro; Hata, Yuki; Kawakatsu, Kazuto; Tanii, Takashi; Onoda, Shinobu; Stacey, Alastair; Kono, Shozo; Kawarada, Hiroshi
Abstract: The nitrogen vacancy (NV) center in diamond is fascinating and has a long spin coherence time. It is applied to magnetic sensors with high sensitivity (∼fT). To achieve a high sensitivity, an aligned NV ensemble is required. This paper presents a new methodology for the fabrication of two-dimensional (2D) aligned NV ensembles by using nitrogen-terminated (111) surface. To realize this, pure diamond growth and high nitrogen coverage on (111) surface were performed. As a result, we have succeeded in producing 2D NV ensembles, with 1 × 10 9  cm −2 . Coherence time T2 was 2.45 μs. Also, Using dynamical decoupling, the decoherence sources were revealed. The alignment ratio along [111] axis was archived 60%. Thermal annealing of the nitrogen termination was introduced to improve the alignment ratio. After that, the alignment rate was up to 73%. This report shows that the aligned 2D NV ensemble has possibility to be applied for multiple quantum devices. Graphical abstract: Image 1 Highlights: 2D aligned nitrogen vacancy ensembles created using nitrogen-terminated (111) surface. Pure diamond growth and high nitrogen coverage were used. The method afforded highly aligned nitrogen vacancy centers. This technique enables nitrogen vacancy centers with multiple quantum application .